The Effect of Corporate Governance and Financial Health on The Value of Companies Registered in Indonesia Stock Exchange - Suaibatul Fitriyah; Makaryanawati Makaryanawati; Slamet Fauzan (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
The main goal to be achieved by a company is to increase its value. Having high company value, the owners will gain higher prosperity. Company value is a particular condition achieved by a company reflected in the stock market price. Strategies to increase it are important. This study aims to determine the effect of corporate governance (X1) on company value (Y) and to determine conditions of financial health (X2) on company value (Y). This research is an associative type of hypothesis testing. Companies used in this study are those listed in the Indonesia Stock Exchange during the 2014-2017 period. The sample selections use purposive sampling with the criteria that the companies are CGPI participants and not engaged in finances with 29 companies as the samples. The analysis technique used is multiple regression. The results of the study show that: 1) good corporate governance does not affect the company value. 2) The condition of financial health has a positive effect on company value. The limitation in this study is the lack of research samples, because there are very few companies that participate in the CGPI ranking program. The results of this study are expected to be used as a reference for future researches, besides that research related to corporate governance should use measurements or other indicators to obtain different results.